Open Stakeholder Consultations at the European Level-Voice of the Citizens? - Marxsen, Christian (European law journal : review of European law in context, 2015)
The European Commission's open consultations of stakeholders are a central mechanism of the attempt to practice participatory governance at the European level and to open the political process to contributions from the societal sphere. This paper analyses the current practice of open consultations as one important operationalisation of participatory governance and as an implementation of Article 11 of the Treaty of the European Union (TEU). It asks whether consultations can be a means to give voice to the citizens and to increase the legitimacy of European institutions. The paper presents an empirical analysis of the field of participants in the consultations. A main finding is that business and industry organisations dominate the consultative process while the participation of citizens and not-for-profit organisations is generally weak. The paper explores to which extent the consultations can, considering the empirical findings, be seen as a suitable way for direct or representative citizen participation.